ASAS PERADILAN SEDERHANA, CEPAT DAN BIAYA RINGAN DALAM PERADILAN TINDAK PIDANA KORUPSI DI PENGADILAN NEGERI MEDAN - Adi Syahputra Sirait (Jurnal AL-MAQASID: Jurnal Ilmu Kesyariahan dan Keperdataan, 2021)
This paper aims to analyze and explain how the implementation of the principles of justice is simple, fast and low cost in the trial of criminal acts of corruption at the Medan District Court based on the Supreme Court Decision Number 022/KMA/SK/II/2011 as lex specialis of law number 48 of the year. 2009 where the trial of corruption cases was carried out by the District Court in the Provincial Capital, the Medan District Court became the Court that examined and tried corruption cases that occurred in districts or cities in North Sumatra Province. This paper uses a normative research method with a case approach, the source of this research is information obtained from interviews conducted with prosecutors and lawyers who handle corruption cases tried at the Medan District Court, then the results of these interviews are analyzed using a doctrinal approach or legal theory. So the results of this study indicate that the corruption trial conducted at the Medan District Court on the basis of the Supreme Court's decision does not reflect the principles of a simple, fast and low-cost trial, on the grounds that the trial takes a lot of time and costs so much, plus the trial was lengthy because the defendant was sick so he had to be treated first and the trial was postponed, but the postponement of the trial had to be attended by the prosecutor and lawyers.